YOSHLARNING JISMONIY SIFATLARINI RIVOJLANTIRISHDA TA’LIM-TARBIYA TAMOYILLARI - Qaljanov, P. (SCIENCE and SOCIETY, 2024)
The principles of physical education provide an approach to the development of a person as a perfect individual in all respects, which contributes to the development of children's physical abilities, motor skills and skills in combination with the implementation of individual child education and comprehensive education.
Keywords: physical education; sport; exercises; activity; development; principle; age groups; action; training; technique; tactics; skills